Influence of pulsed Nd:YAG laser oscillation energy on silicon wafer texturing for enhanced absorption in photovoltaic cells - Huda Abdul Razak N.; Amin N.; Sajedur Rahman K.; Pasupuleti J.; Md. Akhtaruzzaman; Sopian K.; Albaqami M.D.; Mohamed Tighezza A.; Alothman Z.A.; Sillanp M. (Elsevier B.V., 2024)
The influence of the Nd:YAG laser's oscillation energy on creating textured surfaces on silicon wafers is investigated in this study. The silicon wafer surfaces were directly ablated by a pulsed Nd:YAG laser beam to create the texturing, which was then examined using UVVis spectroscopy, AFM and FESEM to determine its characteristics. The reflectance was reduced up to 15% after laser texturing of multicrystalline silicon wafers. The silicon surface suffers from structural defects and a laser damage layer as a result of the laser texturing process, which in turn has an effect on the lifespan of the photo-generated carriers. To compensate for the laser damage layer, the silicon surface was cleaned with diluted KOH (15%) to remove undesirable particles and the oxide layer. Surface roughness and reflectance in silicon solar cells were changed depending on the laser oscillation energy utilized for texturing. The roughness and reflectance were measured using AFM and UVVis, respectively. The laser oscillation energy of 84 J/p had the highest average roughness of 0.2104 m and the lowest reflectance of 5%. As a result, standard silicon solar cell devices revealed photovoltaic conversion efficiencies of roughly 7.5% and 5.0% for laser-textured grid and one-dimensional line patterns, respectively. 2023 The Authors